2018
DOI: 10.1007/s00213-018-5026-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of abstinence on MDMA and cocaine self-administration in rats

Abstract: The selective reduction of MDMA self-administration following abstinence is consistent with the idea that MDMA-stimulated 5-HT release is inhibitory to MDMA self-administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
1
10
1
Order By: Relevance
“…Amongst those characteristics is an escalation of drug intake as a function of repeated testing and drug-seeking following extinction of self-administration (Ahmed & Koob, 1998;Mandt et al, 2015;Mantsch et al, 2004). Under some conditions, repeated MDMA self-administration led to an escalation of intake (Ball et al, 2007;Highgate & Schenk, 2018;van de Wetering & Schenk, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst those characteristics is an escalation of drug intake as a function of repeated testing and drug-seeking following extinction of self-administration (Ahmed & Koob, 1998;Mandt et al, 2015;Mantsch et al, 2004). Under some conditions, repeated MDMA self-administration led to an escalation of intake (Ball et al, 2007;Highgate & Schenk, 2018;van de Wetering & Schenk, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When daily session lengths are increased (e.g. 6 hours per day), however, a significant escalation in drug intake has been observed over successive test sessions (Ahmed & Koob, 1998;Ahmed, Walker, & Koob, 2000;Highgate & Schenk, 2018;Kitamura, Wee, Specio, Koob, & Pulvirenti, 2006;O'Dell et al, 2007;A. J. Roberts, Heyser, Cole, Griffin, & Koob, 2000).…”
Section: Studying Addictionmentioning
confidence: 99%
“…Response rates for MDMA are initially low, and acquisition of reliable MDMA self-administration (1 mg/kg/infusion) typically requires around 15, 2-hour daily sessions (Schenk et al, 2012). In contrast, the self-administration of cocaine, amphetamine, or methamphetamine is usually reliably acquired within a few days (Carroll & Lac, 1997;Highgate & Schenk, 2018;Maan, Highgate, & Schenk, 2020;Schenk et al, 2007).…”
Section: Mdma Self-administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…While both are amphetamine analogues, methamphetamine and MDMA have different pharmacological profiles, at least following acute administration (Baumann et al, 2002(Baumann et al, , 2005. However, repeated MDMA exposure produced selective deficits in 5HT neurotransmission and it has been suggested that these deficits might contribute to the acquisition of MDMA self-administration (Aronsen et al, 2016;Bradbury et al, 2014;Highgate and Schenk, 2018;Oakley et al, 2014;Schenk, 2011). Methamphetamine exposure can also produce deficits in 5HT neurotransmission (Volz et al, 2007), but 5HT does not appear to play a prominent role in methamphetamine self-administration.…”
Section: Comparison Of Methamphetamine and Mdmamentioning
confidence: 99%